Efeitos da estabilização da embocadura do canal de Sernambetiba e replenamento do estoque de areia na morfodinâmica da Praia da Macumba - RJ - Silva, Gabriele dos Santos (2019)
Understanding beach morphodynamics is essential for coastal management, given that changes in the physical environment directly affect sediment transport. This study aims to analyze the morphodynamic responses of Macumba beach to the implementation of jetties in the mouth of the Sernambetiba channel and beach nourishment of Macumba beach, considering a year of typical conditions and a year after the occurrence of very strong El Niño. For this, the morphodynamic model of the SisBaHiA® was used. The results indicated that the current circulation pattern is determined by the astronomical tide in the river and channel region, the incidence of waves in the shoreline and the meteorological tide in the rest of the modeling domain. In the scenario without intervention and wave climate of one year after El Niño, the most vulnerable region to wave incidence is that located west of the Itapuã rock, with the highest erosion rates, while the region of Sernambetiba canal mouth remains silted throughout the simulation period. With the proposed interventions there was a one-third reduction in erosion and a reduction of 0,5 m to 0,2 m in siltation rates in the scenario with wave climate of one year after El Niño. In the scenario with intervention and typical wave climate, erosion rates also decreased significantly, reaching 0,8 m, and there was no sediment accumulated at the mouth of the Sernambetiba channel.